Present in Body or Just in Mind: Differences in Social Presence and Emotion Regulation in Live vs. Virtual Singing Experiences - Fancourt, Daisy; Steptoe, Andrew (Frontiers in Psychology, 2019)
Over the past two decades, many musical experiences have become mediated by digital technology, including the distribution of music online, the generation of new content and participation in virtual musical experiences. However, whether virtual musical experiences lead to different experiences of social presence or differential use of emotion regulation strategies (ERSs) compared to live musical experiences remains un-researched. We compared the experiences of 1,158 singers in a virtual choir (VC) with the experiences of 1,158 singers from a live choir using propensity score matching based on a range of demographic, social and musical factors. Participants in VCs reported a slightly greater feeling of social presence than participants in live choirs [t(1157) = -19.85, p < 0.002]. They also made less use of overall ERSs [t(1157) = 3.10, p = 0.002], avoidance strategies [t(1157) = 4.51, p < 0.001], and approach strategies [t(1157) = 3.34, p < 0.001]. However, they made greater use of self-development strategies [t(1157) = -3.11, p = 0.002]. Social presence was associated with greater use of all ERSs. This study showed that although a sense of social presence in a choir is not reduced by engagement in VCs compared to live choirs, there is a lowered use of ERSs when engaging in VCs. However, as the difference in use of ERSs is relatively modest, virtual musical experiences may still have a role to play in supporting those who cannot engage in live experiences such as people who are socially isolated.